Ameliorative Effects of Honey, Propolis, Pollen, and Royal Jelly Mixture against Chronic Toxicity of Sumithion Insecticide in White Albino Rats - Atef M.K. Nassar; Yehia M.M. Salim; Khalid S.A. Eid; Hazem M. Shaheen; Abdullah A. Saati; Helal F. Hetta; Amr Elmistekawy; Gaber El-Saber Batiha (Molecules, 2020)
Sumithion (Fenitrothion) (SUM) is an organophosphorus insecticide used to combat a wide variety of plant pests. Exposure to SUM causes significant toxicity to the brain, liver, kidney, and reproductive organs through, for example, binding to DNA, and it induces DNA damage, which ends with oxidative stress. Therefore, the present study aimed to examine the protective role of bee products: a mixture of honey, propolis, palm pollen, and royal jelly (HPPJ) against SUM-induced toxicity. Twenty-four male albino rats (Rattus norvegicus) were classified into four groups, each containing six rats: control (corn oil), SUM (85 mg/kg; 1/20 LD50), HPPJ, and SUM + HPPJ once daily for 28 consecutive days. Blood samples were gently collected in sterilized ethylenediaminetetraacetic acid (EDTA) tubes for blood picture analyses and tubes without anticoagulant for serum isolation. Serum was used for assays of enzymatic and biochemical characteristics. The results revealed that SUM increased the weights of the liver, kidney, and brain as well as the enzymatic activity of glutathione peroxidase (GP), serum superoxide dismutase (SOD), and glutathione-S-transferase (GST). Additionally, SUM significantly increased the activity of lactate dehydrogenase (LDH), alkaline phosphatase (ALP), and γ-glutamyltransferase (γ-GT) and glucose, uric acid, and creatinine contents, while decreasing the acetylcholine esterase (AChE) activity and total lipids and total protein content. Furthermore, because of the inclusion of phenolic, flavonoids, terpenoids, and sugars, the HPPJ mixture counteracted the hematological, renal, and hepatic toxicity of SUM exposure.